The effects of high-intensity hypoxic training on 50m freestyle swimming performance - Grznár, L.; Labudová, J.; Púzser, K.; Odráška, L. (Journal of Physical Education and Sport, 2025)
This study investigates the effects of a six-week high-intensity hypoxic training intervention on adolescent competitive swimmers. Sixteen participants were divided into two groups: an experimental group (EX), which performed hypoxic training sessions twice per week, and a control group (CG), which followed a standard training program. Performance was assessed through four specific tests: static apnea duration, breath-hold distance, 50-meter freestyle time, and number of breaths taken during exercise. To assess both the statistical and practical significance of the intervention, the effect size coefficient "r" (Effect Size, ES) was calculated for each variable. The EX group demonstrated statistically significant improvements across all measured parameters. Specifically, static apnea duration increased by 9.63% (p < 0.05; ES = 0.26), breath-hold distance improved by 7.31% (p < 0.05; ES = 0.38), number of breaths decreased by 47.92% (p < 0.05; ES = 1.57), and 50-meter freestyle time decreased by 1.97% (p < 0.05; ES = 0.89). In contrast, the CG showed only marginal improvement, with a statistically significant change observed only in the 50-meter freestyle time (1.06%, p < 0.05; ES = 0.52). These results are consistent with previous research suggesting that controlled hypoxic training enhances physiological adaptations, including improved oxygen utilization and respiratory efficiency. These findings support prior research suggesting that controlled hypoxic exposure leads to beneficial physiological adaptations, including enhanced oxygen utilization, respiratory control, and improved athletic performance under limited oxygen availability. The study highlights the value of integrating hypoxic training into swim programs for improving both breath control and endurance in young athletes.